Research of the power effectiveness of the traction electrotechnical complex motion trajectory realization in a trolleybus with peak motor efficiency - Losina, K.; Yakimets, S. (НГУ, 2013)
The requirements imposed on traction electrotechnical complex are increasing day by day. This is ex-pressed in raising evaluation of quality, ease of implementation, efficiency, reliability and performance when the necessary criteria for optimality [1] are met. The control systems of traction electrotechnical complex (TEC) of city electric transport are diverse. They are formed by power electric circuits, which include traction DC motors and devices, machines and converters and auxiliary circles, which include auxiliary electrical machines, heating and lighting devices.
Keywords: КПД электродвигателя; коэффициент полезного действия механизмов и машин; траектория движения; троллейбус; тяговый электротехнический комплекс; энергетическая эффективность